Essays on R&D investments, market structure and welfare - Saboori Memar, Ahmad Reza; Justus Liebig University Giessen (My University, 2013)
The firms´Investments in research and development (R& D) are of key importance both for the overall economic development and for competition in oligopolistic market structures. While both product and process R& D can yield higher consumer welfare, it is often assumed that competition is a necessary condition for the implementation of this consumer-welfare-enhancing potential. This belief provides the background for the actions of competition authorities, such as prevention of price discrimination as well as mergers and acquisitions, in order to ensure genuine and undistorted competition. This is the point where this dissertation comes in. It investigates the firms´ R& D incentives in different oligopolistic market structures depending on the intensity of competition in the market. Moreover, this dissertation scrutinizes the above practices of competition authorities.

Die Forschungs- und Entwicklungsinvestitionen der Unternehmen sind sowohl für die gesamtwirtschaftliche Entwicklung als auch für den Wettbewerb in oligopolistischen Industriestrukturen von zentraler Bedeutung. Während neue Produkte und verbesserte Produktionsprozesse prinzipiell zu einer Erhöhung der Konsumentenwohlfahrt führen können, wird häufig unterstellt, dass erst Wettbewerb dazu führt, dass dieses wohlfahrtssteigernde Potenzial auch tatsächlich realisiert wird. Diese Überzeugung bildet den Hintergrund für die Aktivitäten der Wettbewerbsbehörden, die z.B. durch die Verhinderung von Preisdiskriminierung sowie die Fusionskontrolle unverfälschten und wirksamen Wettbewerb sicherstellen wollen.An dieser Stelle setzt meine Dissertation an. Sie untersucht, welche Forschungsanreize sich den Unternehmen in verschiedenen oligopolistischen Industriestrukturen in Abhängigkeit von der jeweiligen Wettbewerbsintensität bieten. Des Weiteren wird die oben angeführte Praxis der Wettbewerbsbehörden hinterfragt.
Aufsätze zu Forschungs- und Entwicklungsinvestitionen, Marktstrukturen und Wohlfahrt
Keywords: research and development; vertical relations; mergers and aquisitions; interbrand and intrabrand competition; process innovation; ddc:330